A methodology for an optimal design of ground-mounted photovoltaic power plants. (15th May 2022) - Barbón, A.; Bayón-Cueli, C.; Bayón, L.; Carreira-Fontao, V.
Abstract: A methodology for estimating the optimal distribution of photovoltaic modules with a fixed tilt angle in ground-mounted photovoltaic power plants has been described. It uses Geographic Information System, available in the public domain, to estimate Universal Transverse Mercator coordinates of the area which has been selected for the installation of the photovoltaic plant. An open-source geographic information system software, Q G I S, has been used. The estimation of the solar irradiance takes into account the variations in the local cloud cover distribution. The optimization process is considered to maximize the amount of energy absorbed by the photovoltaic plant using a packing algorithm (in Mathematica™ software). This packing algorithm calculates the shading between photovoltaic modules. This methodology can be applied to any photovoltaic plant. Different rack configurations and tilt angles are incorporated in the study to account for the characteristics of the irregular shape of the land. The most used rack configurations in photovoltaic plants are the 2 V × 12 configuration (2 vertically modules in each row and 12 modules per row) and the 3 V × 8 configuration (3 vertically consecutive modules in each row and 8 modules per row). Codes and standards have been used for the structural analysis of these rack configurations. For this purpose, the wind loads, the snow loads, the weight of the structure, the weight of the photovoltaic modules, and combinations thereof have been calculated. This analysis has been performed with AutoDesk Robot Structural Analysis software for the different rack configurations. A detailed cost analysis of the most used rack configurations in photovoltaic plants has been presented. The levelized cost of the produced electricity efficiency is calculated for each rack configuration. The methodology has been applied in Sigena I photovoltaic plant located in Northeast of Spain. The current rack configuration used in this photovoltaic plant is the 2 V × 12 configuration with a tilt angle of 30 (°). The configurations 3 V × 8 configuration with a tilt angle of 14 (°) and 2 V × 12 configuration with a tilt angle of 22 (°) are the best options proposed by the optimization algorithm. The results show that the 3 V × 8 configuration with a tilt angle of 14 (°) increases the amount of energy captured by up to 32.45% in relation to the current configuration of Sigena I photovoltaic plant with a levelized cost of the produced electricity efficiency of 1.10. In the other hand, the 3 V × 8 configuration increases the amount of energy captured by up to 19.52% in relation to the 2 V × 12 configuration with a tilt angle of 22 (°) with a levelized cost of the produced electricity efficiency of 1.05. The 3 V × 8 configuration is the one which has the lowest cost for the same number of photovoltaic modules. The 2 V × 12 configuration with a tilt angle of 30 (°) increases the cost by up to 32.48% in relation to a 3 V × 8 configuration with a tilt angle of 14 (°). Highlights: A new methodology for an optimum design of ground-mounted PV power plants. The 3V × 8 configuration is the best option in relation to the total energy captured. The proposed solution increases the energy a 32% in relation to the current one. The 3V × 8 configuration is the cheapest one. The LCOE efficiency of the 3V × 8 configuration is the best: 1.10.